PROTEIN-CALORIC RESTRICTION DURING LACTATION HAS A TRANSGENERATIONAL EFFECT IN GLUCOSE HOMEOSTASIS OF MALE RATS (Arquivos do Mudi, 2023)
Experimental and epidemiological studies demonstrated an important association betweeninsults in sensitive stages of development and metabolic syndrome at adulthood.Developmental Origins of Health and Disease (DOHaD) concept indicates that pregnancy andlactation are windows to metabolic programming, once in these phases, occurs a peak ofneuronal development. There is a gap in the study of the transgenerational effect of insultsperformed in programming windows, especially when it comes to malnutrition. FemaleWistar rats were submitted to a protein-caloric restriction during the first 14 days of lactation(LP, low-protein group) or a normal-caloric diet through the lactation (NP, normal-proteingroup). At 70 days old these females were mated with a control male rat. The offspring (F2generation, NP and LP groups) were fed with normal-caloric diet and were euthanized at 21days old to blood collection and biometric analysis. There were no differences betweengroups in body weight at weaning. Also, retroperitoneal, periepididymal and mesenteric fatpads were similar between NP and LP animals. We showed an 11% (PË‚0.05) increase inbrown adipose tissue weight in LP group. Fasting glucose was increased by 99% (PË‚0.05) inLP groups, without alteration in fasting insulin levels. We conclude that protein-caloricrestriction during lactation has a transgenerational effect in male rats, altering the glucosehomeostasis.